Instantaneous Bandwidth Enhancement for Variable Inclination Continuous Transverse Stub Antenna - Zheng Liu; Jian Zhang; Xue Lei; Tianpeng Li; Jun Gao; Zhijian Xu (International Journal of Antennas and Propagation)
In this paper, a method was developed to achieve the instantaneous bandwidth enhancement of a variable inclination continuous transverse stub (VICTS) antenna. The aperture of the VICTS antenna was divided into a subarray, and the true-time delay was introduced to reduce the dispersion of the antenna. The method has low loss and is suitable for the entire beam scanning range. To demonstrate this method, a proposed VICTS antenna composed of 2 × 2 subarrays was designed and simulated. Compared with the traditional VICTS antenna of the same aperture size, the gain loss was reduced by at least 52% and the 3/4-dB gain-loss bandwidth increased from 2.5% to 4.2%. The impedance bandwidth of 16.7% with the S11 value of each subarray below −15 dB was achieved, and the sidelobe of the whole antenna was below −10 dB. The antenna radius was 0.34 m, and the aperture efficiency was 14.8%. The proposed antenna is a suitable candidate as a gateway station antenna for low earth orbit (LEO) satellite communication.